Inequality and Economic Growth : The Role of Initial Income - Brueckner, Markus; Lederman, Daniel (World Bank, Washington, DC, 2018)
This paper estimates a panel model in which the relationship between inequality and gross domestic product per capita growth depends on countries' initial incomes. Estimates of the model show that the relationship between inequality and gross domestic product per capita growth is significantly decreasing in countries' initial incomes. The results from instrumental variables regressions show that in low-income countries, transitional growth is boosted by greater income inequality. In high-income countries, inequality has a significant negative effect on transitional growth. For the median country in the world that in 2015 had a purchasing power parity gross domestic product per capita of around US$10,000, instrumental variables estimates predict that a 1 percentage point increase in the Gini coefficient decreases gross domestic product per capita growth over a five-year period by over 1 percentage point; the long-run effect on the level of gross domestic product per capita is around -5 percent.